Evaluation of on-Farm Drainage System in Nigeria: A Review - Otuaro, E. A.; Adewumi, J. K. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2024)
Drainage involves the removal of the excess water on the farm to improve the aeration and trafficability of soils in regions characterized by seasonal high-water tables. There is no doubt that drainage is intrinsically linked to crop yield. A well-drained soil reduces water stress on crops and improves root development, which is required to increase crop yields and food production quality. Nigeria is committed to a national policy that ensures sustainable development based on proper management of the environment to meet the needs of the present and future generations. This demands positive and realistic planning that balances human needs against the potential that the environment has for meeting them. Management strategies must be implemented to achieve effective and efficient drainage systems. The existing on-farm drainage systems were evaluated and found ineffective and efficient; thus, modifications are required to improve the conditions at various locations in Nigeria.